الأبوة من الرضاع حكمها وآثارها: (Parenthood Through Breastfeeding: Its Ruling and Effects) - ماجد بن محمد بن سالم الكندي; محمد سعيد بن خليل المجاهد (At-Tajdid - Intellectual Refereed Journal, 2024)
The research aims to elucidate the jurists' disagreement on whether breastfeeding creates a prohibitive relationship, by tracing their opinions to their origins, and examining the reasoning behind prohibitive breastfeeding and its implications. The research addresses the following questions: What are the jurists' opinions on breastfeeding as a prohibitive cause, and what are the arguments and objections of each group? What is the preferred opinion on the cause of prohibitive breastfeeding, and what are the implications of establishing a breastfeeding relationship? The study employed both comparative descriptive and analytical deductive methodologies. The research concluded with several key findings, the most important of which is that breastfeeding is indeed a prohibitive cause within the family and its jurisprudence, as indicated by Sharia evidence. The opposing evidence is interpreted and does not contradict the prohibitive evidence. The reason for prohibitive breastfeeding is a valid contract with the wet nurse, establishing a breastfeeding relationship for anyone nursed by the wife attributed to her husband, whose children are attributed to him. Establishing a breastfeeding relationship results in marriage prohibitions and allows for the permissibility of entry, touching, seclusion, and travel. However, prohibitive breastfeeding does not entail the inheritance, financial support, and similar rulings of a blood relationship. Keywords: milk for the male, breastfeeding relationship, breastfeeding, Al-Qa’is.